2009
DOI: 10.1080/14786410802625279
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of bioactive triterpenoid saponin from the seeds ofCassia angustifolia

Abstract: A novel oleanen type triterpenoid glycoside has been isolated from butanolic seed extracts of Cassia angustifolia. Its structure was elucidated as 3-O-{beta-D-glucuronopyranosyl-(1 --> 4)-[beta-D-galactopyranosyl-(1 --> 2)]-beta-D-xylopyranosyl-(1 --> 3)-beta-D-glucopyranosyl}-2, 16alpha-dihydroxy-4, 20-hydroxy methyl olean-12-ene-28-oic acid on the basis of spectral evidence (i.e. FTIR, (1)H NMR, (13)C NMR and FAB-MS data). The isolated saponin was tested for its antifungal activity, where the maximum inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The current study also showed that C. angustifolia exhibits potential fungicidal property against C. albicans . It was shown earlier that saponins, active ingredients of C. angustifolia, were involved in antifungal activity against Colletotridium dematium [32]. It was reported earlier that a butanol extract of C. angustifolia exhibited antifungal activity against Aspergillus terrus , A. flavus and A. niger [31].…”
Section: Discussionmentioning
confidence: 99%
“…The current study also showed that C. angustifolia exhibits potential fungicidal property against C. albicans . It was shown earlier that saponins, active ingredients of C. angustifolia, were involved in antifungal activity against Colletotridium dematium [32]. It was reported earlier that a butanol extract of C. angustifolia exhibited antifungal activity against Aspergillus terrus , A. flavus and A. niger [31].…”
Section: Discussionmentioning
confidence: 99%
“…The laxative effect of this natural product has been linked to its content of anthraquinone glycosides 5. The antifungal activity6 of senna has been demonstrated previously and linked to a triterpenoid glycoside present in the butanolic seed extracts of senna. In addition, a study has demonstrated that an aqueous extract of senna can produce DNA (deoxyribonucleic acid) lesions but cannot induce cytotoxic or mutagenic effects in Escherichia coli cultures; the senna extract has also exhibited an antioxidant/antimutagenic effect in Escherichia coli cultures 7.…”
Section: Introductionmentioning
confidence: 74%
“…The flavonoids kaemferol, kaemperin, rhein and isorhamnetin are also present in cassia ( Nair et al, 2002 ). Additionally, butanolic triterpenoid glycoside has been isolated from seeds extracts ( Khan and Srivastava, 2009 ). Various compounds such as nigrin, cathartic acid, Rhamnetin, gluco-sennin, emodin and salicyclic acid are also extracted from cassia ( Sorina et al, 2017 ) and could be used as an alternative medicine to treat the symptoms of COVID-19 ( Biswas et al, 2021 , Khan et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%